-8x+10=-9x+17

Simple and best practice solution for -8x+10=-9x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+10=-9x+17 equation:


Simplifying
-8x + 10 = -9x + 17

Reorder the terms:
10 + -8x = -9x + 17

Reorder the terms:
10 + -8x = 17 + -9x

Solving
10 + -8x = 17 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
10 + -8x + 9x = 17 + -9x + 9x

Combine like terms: -8x + 9x = 1x
10 + 1x = 17 + -9x + 9x

Combine like terms: -9x + 9x = 0
10 + 1x = 17 + 0
10 + 1x = 17

Add '-10' to each side of the equation.
10 + -10 + 1x = 17 + -10

Combine like terms: 10 + -10 = 0
0 + 1x = 17 + -10
1x = 17 + -10

Combine like terms: 17 + -10 = 7
1x = 7

Divide each side by '1'.
x = 7

Simplifying
x = 7

See similar equations:

| X^2-8x+16/3x^2-6x-24/2x+5 | | 7[x+2]=-49 | | 5ab-8+7ab-2a= | | 9z^3+4z=12z^2 | | 15n^2+17n+6=10 | | x^2+13=134 | | 5a^2-24a+16=0 | | 5z+3=128 | | 7+ln(27x)=28-2ln(x) | | 13x+7=12x-3 | | -m+2=0 | | 3u^9*2x^4u^4*5x= | | -29/41-(-12/41) | | 6x^2-13=281 | | 1-3v=-20 | | 15n^2+17n+6=0 | | 6x-13=281 | | 1+4b=5 | | 1x/4-1=1x/7+2 | | 5+4m=29 | | 2-2p=6 | | 1.7=fraction | | -9=-14+b | | 0.285x^2-2x+2=0 | | 16=18+z | | x/2+17=22 | | 2p+5=25 | | -17=-15+x | | f(x)=895+30g | | 15n^2+17n=4 | | -2=-20+y | | -5b+4=39 |

Equations solver categories